2012
DOI: 10.1515/plm-2012-0006
|View full text |Cite
|
Sign up to set email alerts
|

A low-cost needle-based single-fiber reflectance spectroscopy method to probe scattering changes associated with mineralization in intervertebral discs in chondrodystrophoid canine species – A pilot study

Abstract: Background and objectives:Intervertebral disc herniation is a common disease in chondrodystrophic dogs, and a similar neurologic condition also occurs in humans. Percutaneous laser disc ablation (PLDA) is a minimally invasive procedure used increasingly for prevention of disc herniation. PLDA is performed on thoracolumbar discs to which the same laser energy is applied regardless of their mineral content. Knowledge of individual disc mineral composition would allow laser energy dosage adjustments and more accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 34 publications
(47 reference statements)
0
19
0
Order By: Relevance
“…As intervertebral disc is nearly avascular , SfRS of intervertebral disc is expected to be nearly devoid of spectral modulation by hemoglobin and thereby responds to the changes in scattering properties of the nucleus pulposus. In our previous study performed on 15 normal and 6 degenerated intervertebral discs of two dogs of chondrodystrophoid species, it was demonstrated that the light scattering as measured by interstitial or percutaneous SfRS from the 6 mineralized discs was generally stronger than that from the 15 normal discs, though notable intra‐subject and inter‐subject variations existed. That pilot study also performed CT and radiography, and CT diagnosed all six degenerated discs whereas radiography missed two degenerated discs.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…As intervertebral disc is nearly avascular , SfRS of intervertebral disc is expected to be nearly devoid of spectral modulation by hemoglobin and thereby responds to the changes in scattering properties of the nucleus pulposus. In our previous study performed on 15 normal and 6 degenerated intervertebral discs of two dogs of chondrodystrophoid species, it was demonstrated that the light scattering as measured by interstitial or percutaneous SfRS from the 6 mineralized discs was generally stronger than that from the 15 normal discs, though notable intra‐subject and inter‐subject variations existed. That pilot study also performed CT and radiography, and CT diagnosed all six degenerated discs whereas radiography missed two degenerated discs.…”
Section: Introductionmentioning
confidence: 93%
“…The reflectance spectrum R tissue ( λ ) of SfRS when the fiber is placed interstitially in a scattering medium or tissue comprises of light scattered from the tissue, light reflected at the fiber/medium interface, and light reflected internally within the fiber paths. By normalizing R tissue ( λ ) according to the following equation Rnorm(λ)=Rtissue(λ)Rwater(λ)Rair(λ)Rwater(λ) where R water (λ) and R air (λ) are the reflectance spectra measured from fiber placed in water and fiber placed in air, respectively, we have Rnorm(λ)=ξ1[μs(λ)dfiber]ρ2ρ1+[μs(λ)dfiber]ρ2exp[μa(λ)L]+ξ2 …”
Section: Normalization Of Single‐fiber Reflectance Spectroscopy Measumentioning
confidence: 99%
See 3 more Smart Citations